Changes in antimicrobial resistance and demographics of UTIs in pediatric patients in a single institution over a 6-year period. Issue 2 (April 2018) - Erol, B.; Culpan, M.; Caskurlu, H.; Sari, U.; Cag, Y.; Vahaboglu, H.; Özumut, S.H.; Karaman, M.I.; Caskurlu, T.
Summary: Purpose: To determine changes in antimicrobial resistance and demographics of UTIs in pediatric patients in a single institution over a 6-year period. Materials and methods: The current study examined outpatient urinary isolates from patients aged <18 years. A retrospective cross-sectional analysis of bacteria isolated from children with UTI was performed between 2009 and 2014. The most common bacterial pathogens were determined in the following four age groups: <2 years; 2–5 years; 6–12 years; and 13–17 years. The study analyzed the prevalence and antibiotic resistance patterns for the six most common uropathogens: Escherichia coli, Proteus, Klebsiella, Enterobacter, Pseudomonas and Enterococcus (Summary table ). The antibiotic resistance pattern for UTI during 2009–2014 was also examined. Results: A total of 6515 urinary cultures was examined. The majority of these isolates were from female patients (66.8%). E. coli was the most common uropathogen overall, but the prevalence of E. coli was higher among females (79.5%) than males (54.9%). The biggest percentage of isolates in males was from children aged <2 years (46.1%). Conversely, the majority of isolates in females were from children aged >6 years (46.8%). Results of antimicrobial resistance for E. coli were the highest for ampicillin (70%) and lowest for meropenem (0.19%). Comparing the hospital network data from 2009 to 2014, E. coli resistance increased for ampicillin (from 47.1% to 89%), trimethoprim-sulfamethoxazole (TMP-SMX) (from 44.8% to 56%) and nitrofurantoin (from 5.3% to 15.1%). In contrast, cephalosporins have maintained low antibiotic resistance. Conclusion: UTI in females was nearly twice as common than in males. E. coli remained the most common pediatric uropathogen. Although widely used in other tract infections, ampicillin was a poor empiric choice for pediatric UTIs. Cephalosporins were appropriate alternatives given their low resistance rates. A successful empirical treatment protocol should be based on local epidemiology and susceptibility rates. Summary Table Antimicrobial resistance rates in urobacteria a E. Coli Klebsiella Proteus Enterobacter Enterococcus Pseudomonas TMP-SMX 51.5 39.7 47.5 29.6 8.5 14.6 Ampicillin 70.1 80.7 40.9 64.8 37.4 18.1 AMC 35.6 35.5 12.7 48.8 4.2 10.4 Nitrofurantoin 9.5 39.1 72.6 25.2 22.6 13.2 Cefuroxime 27.6 33.0 9.2 43.2 3.1 20.1 Ceftriaxone 12.6 14.1 1.1 20.2 2.1 18.1 Cefazolin 27.7 30.8 18.3 52.1 4.2 9.7 Ceftazidime 15.3 22.4 2.3 27.7 1.6 21.5 Gentamicin 14.4 11.9 9.6 5.5 2.3 16.7 Ciprofloxacin 9.0 4.4 2.3 0 18.6 9.1 PTZ 4.1 9.9 0.4 11.0 0 7.6 Imipenem 0.5 1.5 3.0 2.5 0 9.0 Aztreonam 11.5 15.7 4.1 13.5 2.1 27.1 Meropenem 0.2 0.9 0.4 0.6 0 11.8 Ertapenem 0.5 2.9 0.4 1.9 0 1.4 Amikacin 1.8 2.4 2.1 2.5 2.5 4.2 AMC, amoxicillin clavulanate; PTZ, Piperacillin-tazobactam; TMP-SMX, trimethoprim-sulfamethoxazole. a Data are presented as %.